Impact of Chronic and Massive Resuspension Mechanisms on the Microphytobenthos Dynamics in a Temperate Intertidal Mudflat. Issue 12 (12th December 2019) - Savelli, R.; Bertin, X.; Orvain, F.; Gernez, P.; Dale, A.; Coulombier, T.; Pineau, P.; Lachaussée, N.; Polsenaere, P.; Dupuy, C.; Le Fouest, V.
Abstract: Microphytobenthos (MPB) resuspension is a key mechanism in the transfer of organic matter from productive intertidal mudflats to terrestrial and marine systems. In this study, we infer on the contribution of physical and biological factors involved in the MPB resuspension. We use a physical‐biological coupled model forced by realistic meteorological and hydrodynamical forcings to simulate chronic (without any concomitant sediment resuspension) and massive (driven by bed failure) resuspension over a year. The model simulates mud surface temperature, MPB growth, and grazing by the gastropod Peringia ulvae . The model suggests that MPB resuspension is the highest in spring tides and at the flood beginning due to high current velocity and low water heights that promote waves‐sea bottom interactions. The seasonal export of MPB biomass is the highest in spring, up to threefold higher than in summer when the export is the lowest. The simulated seasonal dynamics of MPB resuspension results from the MPB biomass concentration in the sediment, physical disturbances, and the bioturbation activity by P. ulvae . Annually, 43% of the simulated MPB primary production is resuspended. The MPB resuspension (60.8 g C·m −2 ·yr −1 ) exceeds the loss by P. ulvae grazing (41.1 g C·m −2 ·yr −1 ). The model suggests that chronic and massive resuspension events are important in the synoptic to seasonal MPB dynamics in temperate intertidal mudflats. Accounting for such processes in the carbon budget assessment in the land‐ocean interface could bring new insights to our understanding of the role played by MPB in the coastal carbon cycle. Plain Language Summary: Intertidal mudflats support a high biological productivity sustained mainly by microalgae living in the sediment. Microalgae form a dense biofilm at the surface of the mud during daytime low tides and fix a high quantity of inorganic carbon into organic carbon through photosynthesis. Microalgae can be resuspended along with the sediment into the sea water during the high tides. Such a transfer is facilitated by episodic physical disturbances like waves and currents modulated by biological drivers. Our study aims to simulate with a numerical model the biologically mediated chronic and physically driven episodic massive resuspension of microalgae on an intertidal mudflat for year 2012. The model is a useful tool to disentangle and estimate the respective contribution of physical and biological factors involved in the microalgae resuspension. At the tidal scale, the resuspension of microalgae is the highest at the flood beginning and during spring tides due to higher current velocity and low water heights that promote waves‐sea bottom interactions and sediment erosion. In 2012, the simulated microalgae resuspension is the highest in spring and the lowest in summer. In the model, the seasonal dynamics of microalgae resuspension results from the microalgae biomass in the sediment, physical disturbances, and the grazers activity at the mud surface that remobilized and facilitated the microalgae resuspension, a process called bioturbation. Annually, 43% of the simulated organic carbon produced by microalgae is resuspended over the year. As microalgae sustain the food web in the mud and in the sea water, their production and resuspension are of key importance for the functioning of coastal ecosystems and the sustainability of economic activity such as shellfish farming. Moreover, estimating the export of organic carbon from the mud to the water is essential to understand the contribution of microalgae biofilms to carbon cycle of the global coastal ocean. Key Points: Seventy‐six percent of microphytobenthos biomass resuspended at flood beginning Spring massive and chronic events represent 20% and 17.5% of the annual microphytobenthos export, respectively Forty‐three percent of annual microphytobenthos primary production is resuspended